Changing bodies in the fiction of Octavia Butler : slaves, aliens, and vampires - Hampton, Gregory Jerome, 1968-2019 (Lexington Books, 2010)
"Changing Bodies in the Fiction of Octavia Butler: Slaves, Aliens, and Vampires is a timely text that critically situates Butler's fiction in several fields of study including American, African-American, gender, and science fiction studies. This bookattempts to avoid excluding as many readers as possible by evading esoteric jargon while still engaging the interdisciplinary discourses that respond to Butler's fiction. The study asserts that Butler's fiction transforms the way the body is imagined with reference to race and gender. This text examines how Butler's fiction is able to cross several genre boundaries while simultaneously reshaping the genre of science fiction."--EBL Choice